Impaired endothelial function in patients with Takayasu's arteritis - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
Objectives Takayasu's arteritis (TAX) is a chronic, inflammatory, large-vessel vasculitis. In this study we aimed to evaluate vascular endothelial function by brachial ultrasonography and to evaluate carotid artery intima-media thickness (CIMT) in patients with TAX compared to systemic lupus erythematosus (SLE) and healthy controls. Methods The study included 32 patients with TAK, fulfilling the 1990 Classification Criteria of American College of Rheumatology (ACR), 18 patients with systemic lupus erythematosus (SLE) classified according to the 1982 ACR Criteria and 20 age- and sex-matched controls. Brachial artery Doppler ultrasonography and bilateral CIMT measurements were performed. Results Basal diameter and nitrate-induced dilatation (NID) values of the brachial artery were similar between the three groups. Flow-mediated dilation (FMD) was markedly reduced in patients with TAK compared to controls (P = 0.0001). CIMT was also significantly increased in the TAK group, compared to the controls (P = 0.0001). In the SLE group, a marked impairment in FMD% was also obtained compared to controls (P = 0.0001). CIMT measurement was similar between the patients with SLE and the controls (P = 0.60, P = 0.05). Conclusions We detected significantly decreased FMD and increased CIMT in TAX, suggesting a marked endothelial dysfunction. Both chronic systemic inflammation and vasculitis might lead to endothelial dysfunction and increased atherosclerosis in TAK, suggesting that management of cardiovascular risk factors are also important in the management of vasculitis.
Keywords: Takayasu arteritis; endothelial dysfunction; CIMT; FMD; ACCELERATED ATHEROSCLEROSIS; CARDIOVASCULAR EVENTS; DYSFUNCTION; CLASSIFICATION; INFLAMMATION; CRITERIA; DISEASE; MARKER; RISK